Queer women and religious individualism - Wilcox, Melissa M., 1972- (Indiana University Press, 2009)
Melissa M. Wilcox explores the complex spiritual lives of queer women in the Los Angeles area. She takes the reader on a tour of a colorful array of religious and secular groups that serve as spiritual resources for these women -- from the well-known Metropolitan Community Churches to Wiccan covens, from the Gay and Lesbian Sierrans to the Sisters of Perpetual Indulgence. Arguing that these women's stories are exemplary cases of postmodern patterns of religious identity, belief, and practice, Wilcox offer.